Should we reconsider cefazolin for treating staphylococcal meningitis? A retrospective analysis of cefazolin and cloxacillin cerebrospinal fluid levels in patients treated for staphylococcal meningitis. (October 2020) - Le Turnier, P.; Gregoire, M.; Deslandes, G.; Lakhal, K.; Deschanvres, C.; Lecomte, R.; Talarmin, J.-P.; Dubée, V.; Bellouard, R.; Boutoille, D.; Leroy, A.-G.; Gaborit, B.J.; et al.
Abstract: Objectives: To assess the meningeal penetration of cefazolin and cloxacillin in individuals treated for methicillin-susceptible staphylococcal meningitis. Methods: We retrospectively identified individuals treated for Staphylococcus meningitis with measurements of cefazolin or cloxacillin concentrations in cerebrospinal fluid (CSF) using a validated assay of liquid chromatography coupled with mass spectrometry at the Nantes University Hospital between January 2009 and October 2019. Staphylococcus meningitis was defined by a compatible clinical presentation and a microbiological confirmation (positive CSF culture or positive specific PCR). Medical charts were retrospectively reviewed to collect microbiological and clinical data, and to assess therapeutic success. Results: Among the 17 included individuals, eight (47%) were treated with cefazolin and nine (53%) with cloxacillin. Median daily dosages of cefazolin and cloxacillin were 8 g (range 6–12 g) and 12 g (range 10–13 g), respectively. Cefazolin and cloxacillin were mainly administered by continuous infusion. Eleven individuals (65%) were men, median (interquartile range (IQR)) age was 54 years (50; 70), 14 (82%) had postoperative meningitis and 3 (18%) had haematogenous meningitis. Median (IQR) antibiotic CSF concentrations were 2.8 mg/L (2.1; 5.2) and 0.66 mg/L (0.5; 0.9) for cefazolin and cloxacillin groups, respectively. Cloxacillin was discontinued in two individuals for therapeutic failure. Conclusions: Patients with staphylococcal meningitis treated with high-dose continuous intravenous infusion of cefazolin achieved therapeutic concentrations in CSF. Cefazolin appears to be a therapeutic candidate that should be properly evaluated in this indication.